Spiritualitas Orang Tua Sebagai Landasan Dalam Membentuk Karakter Anak Di Keluarga - Betty Hutabarat; Sri Handayani; Talizaro Tafonao (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
The purpose of writing this article is to explain the importance of exemplary parental life in shaping character in the family. The study departs from the author's empirical observations, that there are some children today who are very good at parental attention and do not reflect Christian character as explained in this article. The method used in writing this article is a descriptive qualitative research method with a literature review approach. The results obtained in this article are that parents must place the family as a place to testify about the exemplary life in Christ, the family as an educational institution for children and Jesus as an exemplary teacher in the family. In this way parents align education and actions in shaping the character of children in the family. Because this is absolutely what parents must do as witnesses of Christ in the family.